Monitoramento de corrosão por potencial de circuito aberto em armaduras embutidas em corpos de prova de argamassa - Hemkemeier, Thiago Alex (2021)
Corrosion is one of the main problems affecting the service life of reinforced concrete structures. To reduce this problem, it is critical to perform periodic maintenance on buildings. There are several corrosion monitoring techniques, and one of the most used is the open circuit potential technique (OCP). However, this technique has experimental parameters that can influence its results. For instance, the use of wetting and drying cycles, the use of different types of the reference electrode, and total and partial immersion in sodium chloride solution (NaCl). Thereby, this study aimed to evaluate some parameters of this technique and analyze their influence on the results, to generate information to the technical and scientific environment about the behavior of steel bars in different situations during the OCP test. The main purpose of the research was to evaluate the OCP technique, but different mixes design were used, with the incorporation of wastes to replace partially the aggregate, to evaluate the performance of these mixes design in exposure to chlorides and check if the OCP technique applies to mortars with the incorporation of wastes. The mixes design used were the normal (NOR), with the incorporation of water treatment plant sludge (WTPS), and with the incorporation of sugarcane bagasse ash sand (SBAS). With this study, it was possible to conclude that the best combination to obtain OCP results more quickly is with wetting and drying cycles and partial immersion of the specimens in the NaCl solution. It was also concluded that the OCP technique is applicable in cementitious matrices with the incorporation of wastes. Mortars with the incorporation of WTPS and SBAS provided an environment with higher protection for steel bars because they showed a later corrosion probability when compared to normal mortar specimens.